Preferences of Consumers in Choosing Sharia Banking Services (Case Study 4 University in Ternate) - Fajri Hatim; Muhdar Muba (Journal of International Conference Proceedings (JICP), 2020)
This study aims to analyze the factors that affect consumer preferences in choosing Islamic banking services. The data were collected by distributing questionnaires, with 186 respondents selected as the samples from four universities in Ternate. Confirmatory Factor Analysis (CPA) was used for the data analysis in which the internal and external factors existed. The interpretation on indicator numbers of each factor was devoted to increase factor interpretation factor and determine models based on loading factor. Overall, the results indicate 11 indicators affecting consumers’ preference to Islamic banking services in Ternate. For one thing, the results of research indicate that consumers’ knowledge about type of banks does not affect their preference. This implies no correlation between them due to no clear understanding about religious affiliation influences to the selection of banks. In addition, the results showed family factors affect the consumers’ preference in choosing banks. It means family support influences the choice. Moreover, numerous product choices do not moderate consumers' preference. This study contends that information from media influences consumers’ preference. The higher the access to information media, the more chances consumers will opt for Islamic bank services. The factor analysis data management result reveals 11 items while KMO test value is 0,793> 0,5. Thus, it is feasible to use. This meaning that support is very influential on the choice, the results mention the product does not affect on the effectiveness of melting is more and more product. The choice of consumers to a product, the result of research mention information from the media on the selection of bank have influence. The higher the access of information media, the more chance consumers choose sharia bank service. The result of data management by using factor analysis is 11 items while KMO value in factor analysis test 0.793>0.5 then KMO value above factor analysis is feasible to use.